A Detailed Survey and Comparative Study of Cooperative Caching Methods for Mobile Ad Hoc Networks - Jain, Devendra K.; Sharma, Sanjay; Yadav, Shashank; Singh, Jitendra (International Journal of Sensors Wireless Communications and Control, 2019)
Mobile Ad Hoc Networks (MANETs) are networks that enable server and clients to impart without any settled foundation. MANET is a quickly developing region of research as it discovers use in different applications. In MANETs, network parceling and the fizzling of a mobile node because of weariness of their battery power can significantly diminish data accessibility. Data caching on the client is generally observed as a successful answer for enhancing data availability. Specifically, cooperative caching based on information sharing and coordination of cached data item among numerous clients is much time-consuming. Various cooperative caching plans have been proposed in the ongoing years. This paper examines the highlights for outlining a good cooperative cache management, and it overviews the current cooperative caching scheme. The paper likewise gives a correlation of the cooperative caching scheme and examines open doors for future research work.
Keywords: Cache discovery